Efektivitas Content-Based Instruction Berbasis YouTube dalam Pembelajaran Bahasa Arab di MA Al-Adli Palembang - Salmani, Sayyid Ahmad; Jumhur, Jumhur; Nazarmanto, Nazarmanto (LPPM Institut Pendidikan Nusantara Global, 2025)
This study is motivated by the low level of student participation and learning outcomes in Arabic language instruction, which is still dominated by conventional methods. Content-Based Instruction (CBI) is considered a relevant approach because it emphasizes language learning through meaningful content, while YouTube emerges as a popular medium that provides authentic and contextual materials. The purpose of this research is to investigate the effectiveness of applying YouTube-based CBI in Arabic language learning at MA Al-Adli Palembang. The research method employed is mixed methods with a quasi-experimental design. The subjects of the study were tenth-grade students, with the experimental class taught using YouTube-based CBI and the control class taught with conventional methods. Data were collected through pre-tests, post-tests, observations, interviews, and documentation, then analyzed quantitatively using the Wilcoxon test and qualitatively through descriptive analysis. The results show that the average post-test score of the experimental class (91.83) was higher than that of the control class (81.5). In addition, students in the experimental group were more active, motivated, and engaged in the learning process. Thus, the implementation of YouTube-based CBI proved effective in improving Arabic learning outcomes while also creating a more interactive, contextual, and digital-friendly learning environment. These findings highlight the potential of integrating CBI with digital platforms like YouTube to support more meaningful and effective language learning experiences, particularly for today’s generation of students who are already familiar with online media.